(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2012)
Abstract The purpose of this study is to determine the competence of heads of Madrasah Aliyah (Islamic Senior High Schools), which includes five competencies, namely Personality Competence, Managerial Competence, Supervision Competence, Entrepreneurial Competence and Social Competence. This study used the survey approach in six provinces, namely: Banten, Jakarta, West Java, Central Java, Yogyakarta and East Java. The findings show that the competence of heads of Madrasah Aliyah (Islamic Senior High Schools) is included in sufficient category with a mean score of 3.8, or about 76% meets the NES. Of the five circumstances, the social competence is the best competence with a score of 4.1 or 82% meets the NES and the entrepreneurial competence is the worst competence with a score of 3.5 or 70% which meets the National Education Standards (NES). Abstrak Tujuan penelitian ini adalah untuk mengetahui kompetensi Kepala Madrasah Aliyah yang mencakup lima kompetensi yaitu Kompetensi Kepribadian, Manajerial, Supervisi, Kewirausahaan dan Sosial. Penelitian ini menggunakan pendekatan survei yang dilakukan di enam propinsi yaitu: Banten, DKI Jakarta, Jawa Barat, Jawa Tengah, DI Yogyakart dan Jawa Timur. Hasil penelitian menunjukan bahwa kompetensi kepala Madrasah Aliyah termasuk kategori cukup dengan rerata skor 3.8 atau sekitar 76% memenuhi SNP. Dari lima kompetensi tersebut, kompetensi sosial merupakan kompetensi terbaik dengan skor 4.1 atau 82% memenuhi SNP dan kompetensi kewirausahaan merupakan kompetensi paling kurang baik dengan skor 3.5 atau 70% memenuhi Standar Nasional Pendidikan (SNP) .